The Influence of Organizational Culture on Employee Commitment Level in the Shared Services Industry in Malaysia - Nadarajan, Logeshwaran (2014)
The main purpose of this study was to study the influence of organizational culture in employee commitment level in an organization, and as there has been many previous researchers which were done in other type of industries, but there has been minimal research done on Shared Service Centres, which is a booming industry. This study focuses on the organizational culture factors which would impact the employee commitment level in the Shared Service Centre (SSC) industry. Shared service industry is the sub unit of the core company which are segregated into another separate entity, and with this rising industry, employee commitment plays an important role in ensuring sustainability. Most companies would invest lots of their resources in hiring, training and ensuring the employees are highly motivated to ensure task assigned are handled efficiently and effectively. Questionnaire was sent and distributed to a foreign SSC company, based in Malaysia, which includes factors such as organization environment, control, types of system used in the organization, identity of the employee, and if the company are people driven or results driven. Upon analysis, the research revealed that environment, control, types of system is the main factors which do influence employee commitment level in the SSC. Additionally, environment in an organization is the primary factor which contributes to employee commitment level compared to the other factors which were analyzed and tested. The study is then concluded with recommendations for further researchers as well as for other stakeholders in the SSC industry.